Harnessing Android Power for Smart Home Automation - Thopate, Kaushalya; Phursule, Rajesh; Kanjalkar, Jyoti; Kulkarni, Radhika V.; Kamlait, Suhas; Pande, Rahul; Biradar, Shivshankar (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In the modern era, homes have evolved into hubs of convenience, efficiency, and control, with various aspects such as lighting, heating, security, and entertainment systems being seamlessly managed through interconnected devices known as home automation systems. The overarching goal of these systems is to enhance a home’s comfort, convenience, and energy efficiency by automating repetitive tasks, enabling remote access, and providing user control. This research paper introduces an innovative system that harnesses the capabilities of Android software to communicate with an Arduino Nano hardware module, acting as a bridge between Android devices and household appliances. The Android application features a user-friendly interface, allowing users to remotely switch appliances on and off, adjust their settings, and receive real-time feedback on their status. This system’s implementation seeks to revolutionize the way we interact with home appliances and, in doing so, aims to enhance overall comfort, safety, and energy efficiency. Additionally, the study delves into emerging trends within the field, including voice recognition, integration of artificial intelligence, and predictive automation. These forward-looking innovations hold the promise of making homes even more adaptable and personalized, elevating the quality of life and contributing to a more interconnected and secure living environment. This research underscores the transformative potential of Android technology in the realm of home automation. It offers insights into how Android-driven automation can enrich our lives, foster sustainability, and create living spaces that are more interconnected and secure.